Using Iraqi Dolomite to Improve some Mechanical andPhysical properties of polyester Resin composites with Jutefibers - nan, nan; nan, nan (Iraqi Journal of Civil Engineering, 2008)
The main objective of the present study is to maintain clear environment by using natural fibers that not cause pollution. Two types of Jute fibers as mat were used to produce ratting polyester composites after treating these fibers with Iraqi dolomite of 0.2, 0.5, 0.7, and 0.9 percentages % where, eight specimens were prepared. Manual casting used to prepared these specimens by using fibers of 2.8 mm diameter between two layers of Resin for all specimens. Mechanical properties tests includes creep, tensile, and hardness by Shore method where best results of creep and tensile strength reduction are given with 0.9% of Iraqi dolomite. Hardness proportional with concentration of dolomite. Physical properties tests includes color, yellowness of color, were the samples exposed to U.V of 254 nm short length wave for 150 hours. The Jute fibers affected the color while the dolomite effects were inconsiderable, also the absorption of acidic and base solutions were proportionate reversely with increasing of dolomite and fibers’ mat percentage. In biological tests, the Fungus growth on composite body decreased with increasing dolomite percentage and no great lost of weight. The present study shown that the Jute fibers in the composite body and concentration of Iraqi dolomite improve the mechanical, physical, and biological properties of polyester Resin composites with Jute fibers.